Construction of radon chamber to expose active and passive detectors - Rojas Hancco, Jhonny Jonnatan (2022)
In this research and development, we present the design and manufacture of a radon chamber (PUCP radon chamber), a necessary tool for the calibration of passive detectors, verification of the operation of active radon monitors as well as diffusion chamber calibration used in radon measurements in air, and soils. The first chapter is an introduction to describe radon gas and national levels of radon concentration given by many organizations. Parameters that influence the calibration factor of the LR 115 type 2 film detector are studied, such as the energy window, critical angle, and effective volumes. Those are strongly related to the etching processes and counting of tracks all seen from a semi-empirical approach studied in the second chapter. The third chapter presents a review of some radon chambers that have been reported in the literature, based on their size and mode of operation as well as the radon source they use. The design and construction of the radon chamber are presented, use of uranium ore (autunite) as a chamber source is also discussed. In chapter fourth, radon chamber characterization is presented through leakage lambda, homogeneity of radon concentration, regimes-operation modes, and the saturation concentrations that can be reached. Procedures and methodology used in this work are contained in the fifth chapter and also some uses and applications of the PUCP radon chamber are presented; the calibration of cylindrical metallic diffusion chamber based on CR-39 chips detectors taking into account overlapping effect; transmission factors of gaps and pinhole for the same diffusion chambers are determined; permeability of glass fiber filter for 222Rn is obtained after reach equilibrium through Ramachandran model and taking into account a partition function as the rate of track density. The results of this research have been published in indexed journals. Finally, the conclusion and recommendations that reflect the fulfillment aims of this thesis are presented.